Challenges of and corrective recommendations for healthcare-associated infection’s case findings and reporting from local to national level in Iran: a qualitative study - Nahid Dehghan-Nayeri; Arash Seifi; Leili Rostamnia; Shokoh Varaei; Vahid Ghanbari; Ali Akbari Sari; Hamid Haghani (BMC Nursing, 2022)
Abstract Background The accuracy of health care−associated infections (HAIs) statistics in many countries is questionable and the main reasons of this inaccuracy are not well-known. The study aim was to explore inhibitors of and corrective recommendations for HAIs case findings and reporting in some of Iran hospitals. Methods Sixteen face-to-face interviews and an expert panel were performed with expertise of infection prevention and control (IPC) programs in hospitals, and Deputies of Health and Treatment in medical university and Ministry of Health from Feb 2018 to May 2019. Using conventional content analysis, code, subcategories and categories were developed. Result Three categories emerged including improper structure preparation, conflict of interest, and inadequate motivation. Allocating distinct budget and adequate staff to IPC programs, developing a user-friendly surveillance system and engaging physicians and nurses for HAIs reporting are the main corrective recommendations accepted by the expert panel. Conclusion Despite the improvement in growing case-findings and reporting of HAIs in Iran, there are many challenges which inhibit accurate case finding and reporting of HAIs. So it is necessary to update the structure, system and rules to reach accurate HAIs data in Iran.